2015
DOI: 10.2166/wst.2015.607
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sonochemical degradation of tetracycline by sulfate radicals

Abstract: Tetracyclines (TCs) are widely used antibiotics in human and veterinary medicine and as growth promoters in the world. Sulfate radical-based advanced oxidation processes have been of great interest due to the high oxidizing potential of sulfate radical to degrade refractory organic pollutants in aqueous solution. In this study, the degradation of antibiotic TC in aqueous solution by silver-activated persulfate (Na2S2O8) in the presence of ultrasound irradiation under various conditions has been investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Obviously, the degradation efficiency of TC was weakened when the pH value was increased from 5 to 11. This is because SO 4 −• is easily converted to HO • under alkaline conditions, and its oxidation potential is lower than that of SO 4 −• 34 . HO • would further react with OH − to produce H 2 O; on the other hand, HO • itself can also produce scavenging reactions, which may all limit the degradation of TC 32,35 .…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the degradation efficiency of TC was weakened when the pH value was increased from 5 to 11. This is because SO 4 −• is easily converted to HO • under alkaline conditions, and its oxidation potential is lower than that of SO 4 −• 34 . HO • would further react with OH − to produce H 2 O; on the other hand, HO • itself can also produce scavenging reactions, which may all limit the degradation of TC 32,35 .…”
Section: Resultsmentioning
confidence: 99%
“…Study results showed that US, US-H 2 O 2 , and ZnO-H 2 O 2 -US follow pseudo first order kinetics. The pseudo first order reaction had the highest coefficient of determination among the studied processes (35). As illustrated in Table 1, the K1 constant increased in US, US- With an increase in the K1 constant, the degradation rate of blue cat 41 also increased (36).…”
Section: Effects Of Zno Nanoparticles On Removal Of Blue Cat 41 In Ulmentioning
confidence: 92%
“…The oxidative radicals generated during acoustic cavitation could be used to oxidise organic pollutants in an aqueous environment [31][32][33][34]. Taking benzoic acid as a simple organic pollutant, its sonochemical degradation is shown in Figure 6.…”
Section: Environmental Remediationmentioning
confidence: 99%